Conciliatory, yet Oppressive: the Kurdish Issue in Syria through the Eyes of Ba’thists from Party Foundation to the 8 March Revolution - Primavera, Mauro (PARTECIPAZIONE E CONFLITTO, 2025)
This paper aims to shed light on the ideological premises and political activities of the Arab Socialist Ba’th Party toward the Kurds before its rise to power in Syria. To start with, the study will retrace the evolution of the Kurdish political movements and their initial interactions with Arab nationalists. Then, it will provide a detailed analysis of the Ba’thist theoretical framework, indicating that, in the early phase of its history, the party did not completely perceive the Kurdish issue as an existential threat to its goals. In addition, the research assumes that ’Aflaq’s "conciliatory" vision began to weaken with the establishment of the United Arab Republic, which caused a radical reshuffling between Arab and Kurd relations. In particular, two dynamics will be investigated: the first one is related to the shift in ideological approach toward the minority issue in Ba’thist literature during the 1950s; the second one focuses on the change in perspective caused by the United Arab Republic and 8 March Revolution.